2014
DOI: 10.1542/peds.2013-3010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Motor and Cognitive Outcome of Acute Encephalitis

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Encephalitis in children can cause significant neurologic sequelae, such as motor and cognitive impairment. Previous reported data are based mostly on questionnaires and clinical assessments.WHAT THIS STUDY ADDS: Significant cognitive impairment, attention-deficit/hyperactivity disorder, and learning disabilities are common after childhood encephalitis. Even children who were considered fully recovered may be significantly affected. Identifiable pathogens, abnormal neuroimaging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
2
42
0
4
Order By: Relevance
“…30 Four studies reported mixed cases of infective encephalitis (e.g. 7,33,35,41 Long-term sequelae A total of 1018 (934 with complete follow-up) survivors of childhood infective encephalitis were evaluated for sequelae; 57.6% (500/868) were male. 7,33,35,41 Long-term sequelae A total of 1018 (934 with complete follow-up) survivors of childhood infective encephalitis were evaluated for sequelae; 57.6% (500/868) were male.…”
Section: Search Resultsmentioning
confidence: 99%
“…30 Four studies reported mixed cases of infective encephalitis (e.g. 7,33,35,41 Long-term sequelae A total of 1018 (934 with complete follow-up) survivors of childhood infective encephalitis were evaluated for sequelae; 57.6% (500/868) were male. 7,33,35,41 Long-term sequelae A total of 1018 (934 with complete follow-up) survivors of childhood infective encephalitis were evaluated for sequelae; 57.6% (500/868) were male.…”
Section: Search Resultsmentioning
confidence: 99%
“…Despite seizures/epilepsy being commonly reported (6–11%) following acute childhood encephalitis, there remains no consensus definition for PE . Most recent studies applied duration of AED usage, although different time thresholds were used including >6 months, >12 months, and ≥3 years .…”
Section: Discussionmentioning
confidence: 99%
“…Despite seizures/epilepsy being commonly reported (6-11%) following acute childhood encephalitis, there remains no consensus definition for PE. [2][3][4] Most recent studies applied duration of AED usage, although different time thresholds were used including >6 months, >12 months, and ≥3 years. 5,6,9 Because most patients with acute symptomatic seizures are treated with AEDs for 3-6 months and weaned by 12 months, we chose a time threshold of AED use of 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long‐term outcome of encephalitis in children has not been well characterized; however, the evidence is concerning for high rates of neurocognitive and behavioural sequelae. A study from Finland showed cognitive and personality problems in over half, and an Israeli study showed moderate to severe sequelae in 63% of children with high rates of behavioural problems; low IQ scores, attention deficit hyperactivity disorder and learning disorders were overrepresented …”
Section: Outcomementioning
confidence: 99%